NONCATALYTIC ESTERIFICATION OF INDUSTRIAL ALCOHOLIC WASTE - KHEDR, M. A.; MANSI, N. M.AL-; ZANATI, E.M. EL- (Biological Sciences - PJSIR, 2022)
A noncatalytic esterification offusel oil was conducted. Studies including the different parameters are investigated to determine the optimum operating conditions for the production of corresponding acetates of the alcoholes of fusel oil, by using the acetic anhydride instead of acetic acid to avoid the use of mineral acid as catalyst. The studied parameters were cited as: molar ratio of reactants and reaction time. The optimum conditions were found to be (2: l/ace.anh.:fusel oil) and 120 min. as molar ratio and time respectively.